Сто лет "Манифеста Коммунистической партии" К. Маркса и Ф. Энгельса: сб. ст. (Госполитиздат, 1948)
Экземпляры: КХ (20110621) / Инвентарный номер: д66701 / Цена: 1.50 / Сис.шифр: 87.3(3/8) / Авт.знак: С 81 / ГРНТИ: 02 / ББК: 87.3(4Гем)5-592